Ocorrência, distribuição e ecologia de macrofungos e mixomicetos em um carste neotropical - Moreira, Mariana Araújo (2025)
The manuscripts presented in this dissertation highlight the importance of studying biodiversity in karst environments, with an emphasis on macrofungi and myxomycetes, organisms not yet recorded in caves in Brazil. Karst areas are characterized by relief formed through the dissolution of soluble rocks such as limestone and dolomite, presenting features with distinct environmental conditions, such as substrate type, humidity, and light, which create specific microhabitats. These environments are rich and varied, harboring species that are often adapted and restricted to these locations. The main objective of the dissertation was to evaluate the occurrence, distribution, and ecology of two groups of organisms, macrofungi and myxomycetes, which, although sharing a common origin, are currently classified separately. The first manuscript, already published, describes the first record of myxomycetes in caves in Brazil. Three species were collected in the karst region of Pains: Arcyriadenudata, Hemitrichiacalyculata, and Metatrichiavesparia. These amoeboid organisms, known for their peculiar life cycle, inhabit humid terrestrial environments and play a significant ecological role in decomposition and nutrient cycling, being fundamental to ecosystem dynamics. The second manuscript reports a new occurrence of Schizophyllum commune in GrutaFurnas, Rio de Janeiro, addressing its morphology, phylogeny, and adaptation. It also includes a checklist of published names in the genus and the designation of a lectotype for S. commune. The third manuscript addresses a gap in research on macrofungi in subterranean environments, evaluating the environmental variables responsible for the presence and absence of these organisms and their influence on distribution in karst environments. The inclusion of these organisms in conservation strategies is crucial, as they act as indicators of ecosystem functioning. Their diversity can be a valuable tool for monitoring habitat quality, especially in areas with high conservation value.